1998
DOI: 10.1289/ehp.98106437
|View full text |Cite
|
Sign up to set email alerts
|

Mode of carcinogenic action of pesticides inducing thyroid follicular cell tumors in rodents.

Abstract: Of 240 pesticides screened for carcinogenicity by the U.S. Environmental Protection Agency Office of Pesticide Programs, at least 24 (10%) produce thyroid follicular cell tumors in rodents. Thirteen of the thyroid carcinogens also induce liver tumors, mainly in mice, and 9 chemicals produce tumors at other sites. Some mutagenic data are available on all 24 pesticides producing thyroid tumors. Mutagenicity does not seem to be a major determinant in thyroid carcinogenicity, except for possibly acetochlor; eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
117
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(124 citation statements)
references
References 57 publications
5
117
0
2
Order By: Relevance
“…Compounds like benzimidazole, which effectively controlled blue mould for more than 20 years, are no longer effective due to the development of resistant populations of P. expansum (Sutton et al 2014), while applications of fludioxonil, pyrimethanil and pyraclostrobin-boscalidcan still provide good control of this disease (Sutton et al 2014). However, it has been shown that pyraclostrabin and fludioxonil are highly to very highly toxic to invertebrates, vertebrates and algae in freshwater and marine systems (Elskus 2012) while pyrimethanil is classified by the US Environmental Protection Agency as a possible human carcinogen since it produces thyroid tumours in rats (Hurley et al 1998; Elskus 2012). Postharvest disease management is thus currently suffering on one hand, as many control strategies are not anymore effective and, on the other hand, as most of the current effective compounds have shown to be toxic and harmful to humans or to aquatic communities.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds like benzimidazole, which effectively controlled blue mould for more than 20 years, are no longer effective due to the development of resistant populations of P. expansum (Sutton et al 2014), while applications of fludioxonil, pyrimethanil and pyraclostrobin-boscalidcan still provide good control of this disease (Sutton et al 2014). However, it has been shown that pyraclostrabin and fludioxonil are highly to very highly toxic to invertebrates, vertebrates and algae in freshwater and marine systems (Elskus 2012) while pyrimethanil is classified by the US Environmental Protection Agency as a possible human carcinogen since it produces thyroid tumours in rats (Hurley et al 1998; Elskus 2012). Postharvest disease management is thus currently suffering on one hand, as many control strategies are not anymore effective and, on the other hand, as most of the current effective compounds have shown to be toxic and harmful to humans or to aquatic communities.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several chloroacetanilides have been shown to cause health hazards, for instance, acetochlor can produce significant incidences of thyroid, bone, granular stomach and nasal cavity tumors in rats, and of liver and lung tumors in mouse [12]. It may also have induced glutathione-dependent cytotoxicity in cultured animal and human cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…Triadimefon was hepatotoxic in chronic studies using Wistar Han rats, causing hepatomegaly at 25 mg/kg/day. At higher doses (90.0 mg/kg/day) triadimefon caused rat thyroid and pituitary adenomas (Hurley et al, 1998). In reproductive studies with rats, 90.0 mg/kg/day decreased male fertility and insemination, and increased plasma testosterone levels with no evidence of testicular histopathology (FAO/WHO, 1982, 1986.…”
Section: Introductionmentioning
confidence: 99%